'Traditional' opera in a 'modern' society: institutional change in Taiwanese xiqu education. Issue 1 (2nd January 2017) - Stenberg, Josh; Hsin-hsin, Tsai
Abstract : All discourses of modernisation in the twentieth century Sinophone world engaged Western, Soviet and Japanese influences and models, and traditional Chinese theatre education was no exception. Although the Republic of China on Taiwan never confined theatre to state-sponsored organisations, a system of theatre education was created to ensure continuity of Jingju (i.e. 'Peking opera') performance, officially identified as the 'national theatre'. Beginning with the 1957 establishment of a private vocational school, Jingju education adopted various (Western-inspired) models, moving from professional training colleges to the present single national post-secondary institution, the 12-year (elementary, secondary and post-secondary) National Taiwan College of Performing Arts (NTCPA). Since nationalisation in 1968, the school has featured in public debate surrounding the place of traditional theatre in Taiwan's shifting cultural politics. Its curriculum and training methods notably came under scrutiny by a legislator in 1970, who found that the school was in desperate need of 'modernisation' to conform to education standards. Yet since actor technique is acquired through kinship-like student‒teacher relations, the adaptation of oral teaching to 'Western' and 'modern' ideas of education, as well as to an academic calendar, remains problematic and contested, with far-reaching implications for theatre performance.